Sex differences in lower limb neuromuscular function and asymmetry among 14-15 years old elite basketball players - Lyu, M.; Pappas, E.; Ding, L.; Qian, H.; Huang, J.; Farragher, J.; Ganderton, C.; Xenos, S.; Lyu, J.; Han, J. (Frontiers in Physiology, 2025)
Objectives: This study aimed to compare inter-limb asymmetry in balance, jumping and strength between male and female basketball players aged 14-15 years old.